2018
DOI: 10.3389/fpls.2018.00733
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Effects of Common Landscape and Nursery Mulch Materials on Weed Control

Abstract: Use of organic mulch materials such as pinebark, pinestraw, or various hardwood chips for weed control is a common practice in residential and commercial landscapes. Mulch can inhibit weed seed germination and growth through light exclusion, acting as physical barrier, reducing available moisture to weed seeds within the mulch layer, and through release of allelochemicals that may inhibit germination or growth of some weed species. Previous and current research on allelopathic chemicals present in mulch have f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 78 publications
0
19
0
1
Order By: Relevance
“…Ovakav na in upotrebe alelopatije ini bogat izvor za sintezu novih jedinjenja (Cornes, 2005). Drugi na in upotrebe je upotreba biljaka sa alelopatskim svojstvima u vidu mal a, to jeste za pokrov zemljišta kako bi se spre ilo nicanje korova, uz pravilnu primenu plodoreda ime bi se zna ajno mogla smanjiti korovska populacija bez upotrebe hemijskih sredstava (Saha et al, 2018). Ovaj postupak se naziva biofumigacija, a obavlja se tako što se biljke iz roda sla ica (Brassica juncea i B. napus) uzgoje do rasta u punom cvetanju nakon ega se mal iraju i dobijena masa se inkorpopirara u zemljište freziranjem.…”
Section: Alelopatijaunclassified
“…Ovakav na in upotrebe alelopatije ini bogat izvor za sintezu novih jedinjenja (Cornes, 2005). Drugi na in upotrebe je upotreba biljaka sa alelopatskim svojstvima u vidu mal a, to jeste za pokrov zemljišta kako bi se spre ilo nicanje korova, uz pravilnu primenu plodoreda ime bi se zna ajno mogla smanjiti korovska populacija bez upotrebe hemijskih sredstava (Saha et al, 2018). Ovaj postupak se naziva biofumigacija, a obavlja se tako što se biljke iz roda sla ica (Brassica juncea i B. napus) uzgoje do rasta u punom cvetanju nakon ega se mal iraju i dobijena masa se inkorpopirara u zemljište freziranjem.…”
Section: Alelopatijaunclassified
“…For example, some members of the family Xanthobacteraceae have the ability to promote plant growth and performance (Suarez et al 2017). The fact that this increased presence of plant growth promoting rhizobacteria in the sawdust treated samples did not induce an improved plant growth of winter barley but the opposite compared to the other treatments points to the presence of allochemicals which may have impaired the growth of the main crop (Saha et al 2018) and, hence, masking positive effects observed on soil microbial diversity.…”
Section: Effects Of the Amendments On Plant Yieldmentioning
confidence: 99%
“…Mulches are plant materials such as straw of the previous crops that are used as a soil cover mainly for conservation of soil moisture (Acharya et al, 2005;Ambayeba, 2018). Mulches hinder seed germination of weeds and stop weed seed plant growth through the discharge of allelochemicals established weeds, however, are tough to regulate with mulches (Saha et al, 2018). Additionally, to weed suppression, use of allelopathic crop residues as surface mulch advantages agricultural property by adding organic interest soil, protective soil wet, up water infiltration into soil, decreasing the impact of raindrops on soil, modifying/regulating soil temperature, enhancing biological activities in soil and dominant wearing away (Teasdale and Mohler, 2000; Kasirajan and Ngouajio.…”
Section: Allelopathy As Mulchingmentioning
confidence: 99%